Examining the Acute Effects of Sleep Restriction and Timing on Energy Balance, Satiety Efficiency and Food Reward in Adults - McNeil, Jessica (Université d'Ottawa / University of Ottawa, 2016)
The main objective of this thesis was to examine the independent effects of sleep duration and timing on appetite, food reward and energy balance. Study 1 investigated the associations between satiety quotient (SQ) with habitual, self-reported sleep duration, quality and timing. No significant associations were noted between SQ and sleep parameters. Short-duration sleepers had a lower mean SQ vs. those with ≥7h sleep/night (P=0.04). Study 2 evaluated associations between changes in sleep duration, efficiency and timing with changes in next day food reward. Greater sleep duration and earlier wake-times were associated with greater food reward (P=0.001). However, these associations were no longer significant after controlling for elapsed time between awakening and completion of the food reward task. Study 3 examined the effects of 50% sleep restriction (SR) anchored during the first (delayed bedtime) or second (advanced wake-time) half of the night on appetite, SQ, food reward, energy intake (EI) and energy expenditure (EE). Greater appetite ratings and explicit high-fat food reward were noted following SR with an advanced wake-time vs. control and SR with a delayed bedtime (P=0.03-0.01). No difference in SQ was noted between sessions. Energy and carbohydrate intakes were greater on day 2 and over 36h in the delayed bedtime vs. control session (P=0.03). Activity EE and moderate-intensity physical activity (PA) time were greater following delayed bedtime vs. control and advanced wake-time on day 1, whereas vigorous-intensity PA time was greater following advanced wake-time vs. delayed bedtime on day 1 (P=0.01-0.04). Greater sleep quality and slow-wave sleep duration between SR sessions were associated with lower EI and increased vigorous-intensity PA time, respectively (P=0.01-0.04). Collectively, these findings suggest that appetite, SQ and food reward are influenced by sleep parameters, but these changes may not alter EI. These findings also suggest that individuals with greater sleep quality in response to SR had greater vigorous-intensity activity time and lower EI.